Hyperbaric Oxygen Therapy for the Treatment of Fournier’s Gangrene: A Review of 34 Cases - Rosa, Isabel (2015)
Introduction: Fournier’s gangrene is a serious necrotizing infection that can be fatal if not promptly attended. Treatment for this condition consists of a combination of surgical debridement, antibiotherapy and supportive care. Hyperbaric oxygen therapy is used as an adjuvant for the optimization of infected tissue oxygenation and for its bactericidal and bacteriostatic effects.Material and Methods: The data presented in this study encompass a period of 25 years of clinical records of patients with Fournier’s gangrene that had been treated at our center with hyperbaric oxygen therapy.Results: A total of 34 patients were treated. The vast majority of patients were males (94.1%) with a mean age of 53.7 years. Urinary tract was the most frequent source of infection and diabetes was most common comorbidity seen in patients. Mortality rate was 20.8%.Discussion: The most common observed comorbidity was diabetes, suggesting diabetes as one predisposing factor. The majority of deceased patients had diabetes, although no significant correlation between diabetes and death was found. The area of residence of patients may affect patients’ referral to these facilities.Conclusions: Although Fournier’s gangrene is a rare condition, it is nevertheless a fatal illness, namely in patients with comorbidities like diabetes. Hyperbaric oxygen therapy is recommended as an adjuvant to conventional therapy and should be considered whenever available. To further assess the role of hyperbaric oxygen therapy, in the treatment of this condition, additional studies should be carried out.